Graficzna prezentacja obiektów symbolicznych - Wilk, Justyna (Visualization of Symbolic Objects, 2006)
The are major concepts of symbolic data analysis explained in the article. Moreover, the visualization of symbolic objects was illustrated (Symbolic Data Table, Zoom Star and Symbolic Objects Language) on the example of Internet e-mail accounts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 86-96